ENFORCING BREACHES OF DIRECTORS' DUTIES BY A PUBLIC BODY AND ANTIPODEAN EXPERIENCES. (3rd July 2015) - Keay, Andrew; Welsh, Michelle
Abstract : A number of commentators, as well as government reports, have argued that the UK's reliance on private enforcement mechanisms for breaches of directors' duties has generally been ineffective. Some argue that provision should be made in statute for public enforcement. Assuming that there is strength in this argument this article asks what form this public enforcement should take. The article considers the way that Australia has proceeded in the past 20 years or so in permitting the public enforcement of breaches of directors' duties, via both criminal sanctions and civil penalties. The argument advanced in this article is that despite the possible advantages that may flow from the introduction of a criminal enforcement regime, such a regime is unlikely to be adopted in the UK. Following an examination of the use that the Australian corporate regulator has made of the civil penalty regime the argument advanced in the article is that the introduction in the UK of a similar regime providing for the making of the same kind of orders would be beneficial.